Crumbs regulates rhodopsin transport by interacting with and stabilizing myosin V - Pocha, Shirin Meher (The Rockefeller University Press, 2011)
The evolutionarily conserved Crumbs (Crb) complex is crucial for photoreceptor morphogenesis and homeostasis. Loss of Crb results in light-dependent retinal degeneration, which is prevented by feeding mutant flies carotenoid-deficient medium. This suggests a defect in rhodopsin 1 (Rh1) processing, transport, and/or signaling, causing degeneration; however, the molecular mechanism of this remained elusive. In this paper, we show that myosin V (MyoV) coimmunoprecipitated with the Crb complex and that loss of crb led to severe reduction in MyoV levels, which could be rescued by proteasomal inhibition. Loss of MyoV in crb mutant photoreceptors was accompanied by defective transport of the MyoV cargo Rh1 to the light-sensing organelle, the rhabdomere. This resulted in an age-dependent accumulation of Rh1 in the photoreceptor cell (PRC) body, a well-documented trigger of degeneration. We conclude that Crb protects against degeneration by interacting with and stabilizing MyoV, thereby ensuring correct Rh1 trafficking. Our data provide, for the first time, a molecular mechanism for the light-dependent degeneration of PRCs observed in crb mutant retinas.